An examination of students’ values reflected in their language use in a blended learning environment - Karalasingam, Shantini (2019)
Values show who we are as individuals, the beliefs we uphold, and the principles we defend for they influence our thoughts and actions. The values portrayed through thoughts are not only translated in the form of actions but also through the language we use to communicate with one another. As such, there is a fundamental need to investigate if values are reflected in one’s choice of language use. The role of language in communication is imperative because the ‘how’ and ‘why’ a word is used are significant and presents more sense than the meaning of the word alone.